Causative Pathogens Do Not Differ between Early, Delayed or Late Fracture-Related Infections - Ruth A. Corrigan; Jonathan Sliepen; Maria Dudareva; Frank F. A. IJpma; Geertje Govaert; Bridget L. Atkins; Rob Rentenaar; Marjan Wouthuyzen-Bakker; Martin McNally (MDPI AG, 2022)
Fracture-related infections (FRIs) are classically considered to be early (0-2 weeks), delayed (3-10 weeks) or late (>10 weeks) based on hypothesized differences in causative pathogens and biofilm formation. Treatment strategies often reflect this classification, with debridement, antimicrobial therapy and implant retention (DAIR) preferentially reserved for early FRI. This study examined pathogens isolated from FRI to confirm or refute these hypothesized differences in causative pathogens over time. Cases of FRI managed surgically at three centres between 2015-2019 and followed up for at least one year were included. Data were analysed regarding patient demographics, time from injury and pathogens isolated. Patients who underwent DAIR were also analysed separately. In total, 433 FRIs were studied, including 51 early cases (median time from injury of 2 weeks, interquartile range (IQR) of 1-2 weeks), 82 delayed cases (median time from injury of 5 weeks, IQR of 4-8 weeks) and 300 late cases (median time from injury of 112 weeks, IQR of 40-737 weeks). The type of infection was associated with time since injury; early or delayed FRI are most likely to be polymicrobial, whereas late FRIs are more likely to be culture-negative, or monomicrobial. Staphylococcus aureus was the most commonly isolated pathogen at all time points; however, we found no evidence that the type of pathogens isolated in early, delayed or late infections were different (p = 0.2). More specifically, we found no evidence for more virulent pathogens (S. aureus, Gram-negative aerobic bacilli) in early infections and less virulent pathogens (such as coagulase negative staphylococci) in late infections. In summary, decisions on FRI treatment should not assume microbiological differences related to time since injury. From a microbiological perspective, the relevance of classifying FRI by time since injury remains unclear.